Determinan Daya Tarik ‘Korean Entertainment’ Pada Konsumen di Manado - Parengkuan, Grifit (JURNAL RISET BISNIS DAN MANAJEMEN, 2013)
The Korean Wave is a way of Korea to transmit its influence or culture into another countries using entertainment. The enchantment of Korean Wave has brought a lot of positive influence on image and culture of Korea in the eyes of international consumers. Manado city as one city that absorb many interesting things from overseas also as soft target for this charming and influencing Korean Wave. The influence of Korean Wave is easily to be absorbed by young generation in Manado especially via entertainment. Korean entertainment businesses with their entire formats start to and spread into so many young people in Manado. This research aims to examine determinant factors in attractiveness of Korean entertainment on young consumers in Manado. Analysis data is factor analysis. The result of research shows that there are six determinant factors in attractiveness of Korean entertainment, namely: psychology, product, closeness, positive stimulus, similarity, and price.